Effect of caffeine on resting-state alpha activity across the human menstrual cycle. - Aziz, Jasmine R.; Oprea, Alexandra; Bissonnette, Jenna N.; Hull, Krista M.; Napier, Kaitlyn; Schryver, Bronwen; Myles, Elizabeth M.; Newman, Randy L.; Perrot, Tara S.; Fisher, Derek J. (Psychopharmacology, 2022)
Rationale: Caffeine is the most consumed stimulant worldwide, and there is great interest in understanding its neurophysiological effects. Resting-state electroencephalography (EEG) studies suggest that caffeine enhances arousal, which suppresses the spectral power of alpha frequencies associated with reduced alertness. However, it is unclear whether caffeine's neurophysiological effects vary across the human menstrual cycle. Objective: The objective of our study was to test whether caffeine's effect on EEG activity differs across the human menstrual cycle. Methods: Fifty-six female participants were randomly assigned to complete the experiment while in either their menstrual (n = 21), follicular (n = 19), or luteal (n = 16) phase. Each participant completed two study sessions in the same menstrual phase, approximately 1 month apart, during which they were administered either a caffeine pill (200 mg, oral) or a placebo pill in a counterbalanced order using a randomized double-blinded procedure. We measured their eyes-closed resting-state EEG approximately 30 min after pill administration and conducted a spectral power analysis at different frequency bands. Results: Caffeine reduced EEG power in the alpha1 frequency band (8–10 Hz), but only for participants who self-reported higher weekly caffeine consumption. Importantly, caffeine's effects did not differ by menstrual phase. Conclusions: We conclude that when studying caffeine's effects on resting-state EEG, participants' baseline caffeine consumption is more influential than their menstrual cycle phase. This study has important implications for the inclusion of menstruating individuals in neurophysiological studies of caffeine.